Realtime garbage collection. - Bacon, David F. (New York ACM, 2007)
It's now possible to develop realtime systems using Java.
Keywords: Software; Operating Systems; Storage management; Garbage collection; Programming languages; Processors; Memory management (garbage collection).; Algorithms; Design